A Model for Culinary Business Development Using Digitalization and Halal Food to Enhance Local Product Competitiveness in Coastal Villages - Siswati, Endang; Rapitasari, Diana; Kharismawati, Ika (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine and analyze the potential and challenges of culinary businesses, the implementation of digitalization and halal certification, and the development of an effective and sustainable model for the